The Identification and Validation of Plasma Membrane Proteins as Potential Therapeutic Targets for Histone H3 Mutant Paediatric High-Grade Gliomas. (1st October 2022) - Snary, Anya; Haque, Farhana; Pickering, James; Rahman, Ruman; Grundy, Richard; Layfield, Robert
Abstract: AIMS: Paediatric high-grade gliomas (pHGG) are the leading cause of cancer-related death in children. Histone H3.3 mutations are an important hallmark of pHGG, but for which their underlying oncogenic mechanisms are incompletely understood. This research aims to identify potential molecular effectors in these tumours that may be therapeutically effective. METHOD: To assess potential molecular effectors, we employed proteomic profiling using LC-MS/MS and determined plasma membrane proteins of the surfactome that are differentially expressed on the surface of H3.3 mutant (G34R, G34V), compared to H3.3-wildtype human glioma cells in culture. RESULTS: Profiling of plasma membrane-enriched fractions identified 34 membrane proteins exclusively detected from H3 G34V mutant cells compared to H3 wild-type cells, and 10 membrane proteins exclusively detected from H3 G34R mutant cells, with 39 membrane proteins shared between both H3 G34R/V genotypes. One of these shared membrane proteins, GLUT1 (glucose transporter) has very recently been reported to be over-expressed and linked to tumour phenotypes in mouse glioma cells manipulated to carry the most common DIPG-associated H3.3-K27M mutation [Miya et al. Neuro-Oncology Advances 2021]. Here, we explore the functional significance of GLUT1 differential expression in H3.3 mutant (G34R, G34V) human glioma cells.